1986
DOI: 10.1002/1098-2337(1986)12:1<21::aid-ab2480120104>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

An empirical typology of violent incidents reported by prison inmates with convictions for violence

Abstract: Forty‐four male prison inmates convicted for violent offences were interviewed, and details of current offence, previous convictions for violence, prison incidents, and violent situations outside of prison were obtained from each offender. Information on victim, circumstances, precipitating events, type of violence, emotions at the time, and the like, was derived for 246 violent incidents. Cluster analysis revealed eight clusters: “criminal” violence to familiar victims, peer violence within prison, domestic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Henderson (1986) researched incidents both within and outside of prison, as described by the perpetrator, and found eight different clusters, in part based on situational factors, which roughly corresponded to eight different types of violence as previously described in other research. Kratcoski (1988) examined situational factors of inmate violence toward guards and found that location of assault, time o f day of assault, and work experience of the correctional officer assaulted, all varied systematically as a function of the assaultive behavior.…”
Section: Situational Studiesmentioning
confidence: 54%
See 2 more Smart Citations
“…Henderson (1986) researched incidents both within and outside of prison, as described by the perpetrator, and found eight different clusters, in part based on situational factors, which roughly corresponded to eight different types of violence as previously described in other research. Kratcoski (1988) examined situational factors of inmate violence toward guards and found that location of assault, time o f day of assault, and work experience of the correctional officer assaulted, all varied systematically as a function of the assaultive behavior.…”
Section: Situational Studiesmentioning
confidence: 54%
“…The usefulness of this type of prediction study has been questioned o n a number of grounds (Henderson, 1986;Megargee & Carboncll, 1985;Shawver, Clanon, Kurdys & Friedman, 1985). The pcrsonality inventories that are most often used, contain little situational or contextual information (Furnham & Henderson, 1982) which hampers their ability to aid in predicting violence that necessarily includes not only a person but also a situation.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of typologies of violence has been proposed and studied [Athens, 1980;Barratt et al, 1999;Henderson, 1986;Megargee, 1966;Polk, 1994;Rasche, 1993;Toch and Adams, 1994]. From a developmental perspective the relationship context is likely to be important.…”
Section: Determinants Of Violence In Different Contextsmentioning
confidence: 99%
“…However, their current attitudes toward violence would make them more amenable to behavior change. Their dissatisfaction with violent behavior may mark an opportunity for an intervention to enable these individuals to deal with conflict situations in a more functional manner (Henderson, 1986). The element of psychological distress is a factor that is considered to be a positive motivational force for behavior change prior to rehabilitation (Ward, Day, Howells, & Birgden, 2004).…”
Section: Discussionmentioning
confidence: 99%